Let u(x,t) is a function, which describes vibration of string. So we can rewrite task in the next form:
"\\dfrac{\\partial^2 u}{\\partial t^2}=b^2\\dfrac{\\partial^2 u}{\\partial x^2}"
"u(0,t)=u(1,t)=0"
"u(x,0)=f(x)=a(x-x^2)"
"\\dfrac{\\partial u}{\\partial t}|\\begin{matrix} \\\\ t=0\\end{matrix}=0"
To solve this task I use a Fourier method.
Let:
"u(x,t)=X(x)*T(t)"
Then,
"T''X=b^2TX''"
"\\dfrac{T''}{b^2T}=\\dfrac{X''}{X}=const=-\\lambda^2"
So we have two tasks:
"1) X''+\\lambda^2X=0"
"2)T''+(b\\lambda)^2T=0"
For the task 1) we have 2 boundary conditions:
"u(0,t)=X(0)T(t)=0=>X(0)=0"
"u(1,t)=X(1)T(t)=0=>X(1)=0"
The first task solution is:
"X(x)=Acos(\\lambda x)+Bsin(\\lambda x)"
From the first boundary condition we have that A=0. The second give us:
"X(1)=Bsin(\\lambda)=0=>\\lambda=\\pi n=>X(x)=Bsin(\\pi n x)"
But we know that:
"||X(x)||=1=>"
"\\begin{matrix} 1\\\\ \\int \\\\ 0 \\end{matrix} |X(x)|^2 dx=\\begin{matrix} 1\\\\ \\int \\\\ 0 \\end{matrix} B^2sin^2(\\pi nx)dx= B^2 * \\dfrac{1}{2}=1"
"B=\\sqrt 2"
For the task 2) we have next solution:
"T(t)=Ccos(\\lambda bt) + Dsin(\\lambda bt)=Ccos(\\pi bn t)+Dsin(\\pi b n t)"
The result of the main task is:
"u(x,t)=\\sqrt 2\\displaystyle\\sum_{i=1}^{\\infty} (Ccos(\\pi n b t) +Dsin(\\pi nbt)) sin(\\pi n x)"
But we also have two initial conditions. The first one:
"u(x,0)=\\sqrt 2 \\displaystyle\\sum_{i=1}^{\\infty} C sin(\\pi nx)=f(x)"
Multiply both side by "\\sin(\\pi kx)":
"f(x)sin(\\pi kx)=\\sqrt 2\\displaystyle\\sum_{i=1}^{\\infty} C sin(\\pi nx)sin(\\pi kx)"
Now integrate both sides with respect to x:
"\\displaystyle\\int_{0}^{1} f(x) sin(\\pi kx)dx=\\sqrt 2\\displaystyle\\int_{0}^{1} C sin(\\pi nx)sin(\\pi kx)dx"
Because trigonomical function are ortogonal, the right side give us:
"\\begin{cases} 0 &\\text {if } k {=}\\mathllap{\/\\,} n \\\\ 1\/2 &\\text {if } k = n \\end{cases}"
So
"C=\\sqrt 2 \\displaystyle\\int_{0}^{1} f(x) sin(\\pi nx)dx\\\\"
"C=\\sqrt 2 a \\displaystyle\\int_{0}^{1} (x-x^2) sin(\\pi nx)dx = -\\dfrac{2a}{(\\pi n)^3}cos(\\pi nx)|\\begin{matrix} 1 \\\\ 0 \\end{matrix} =-\\dfrac{2a}{(\\pi n)^3}(cos(\\pi n)-1)=\\dfrac{4a}{(\\pi (2n-1))^3}"
The second initial condition:
"\\dfrac{\\partial u}{\\partial t}|\\begin{matrix} \\\\ t=0\\end{matrix} = \\sqrt 2 \\pi na\\displaystyle\\sum_{i=1}^{\\infty} Dsin(\\pi n x)=0=>D=0"
So the answer is:
"u(x,t)=\\dfrac{4a\\sqrt 2}{\\pi ^3}\\displaystyle\\sum_{i=1}^{\\infty} \\dfrac{1}{(2n-1)^3}cos(\\pi (2n-1) b t) sin(\\pi (2n-1) x)"
Comments
Leave a comment